Geometria analítica e vetores: uma análise com estudantes do ensino superior. - MARTINS, Antonio Alison Pinheiro (2018)
The present work seeks to analyze the knowledge of students of higher education on analytical geometry and vectors. A study was carried out, relating the contents covered from the first concepts of analytical geometry, studied in basic education, to the study of vectors in the plane and in space, worked in Higher Education. The methodological structure consisted of the collection and analysis of data on resolution and knowledge of vectors, occurring in two stages. In the first one the students answered a questionnaire containing 11 questions involving the concepts of vectors and their properties, already in the second an interview was made based on the answers obtained in the first stage. The analysis of the data occurred through the examination of the answers, seeking to identify the concepts of Analytical Geometry, which are the conceptual basis for the study of Vector Algebra. The students presented their own definitions and at the same time based on theory. It is verified that mathematical concepts seen in high school are often raised to support the study of vectors.